SARS-CoV-2 seroprevalence and associated factors in Manaus, Brazil: baseline results from the DETECTCoV-19 cohort study. (September 2021) - Lalwani, Pritesh; Salgado, Bárbara Batista; Filho, Ivanildo Vieira Pereira; da Silva, Danielle Severino Sena; de Morais, Thiago Barros do Nascimento; Jordão, Maele Ferreira; Barbosa, Aguyda Rayany Cavalcante; Cordeiro, Isabelle Bezerra; Neto, Júlio Nino de Souza; de Assunção, Enedina Nogueira; dos Santos, Rafaella Oliveira; Carvalho, Nani Oliveira; et al.
Highlights: The prevalence of anti-severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) antibodies was 29.10% (19 August 2020 to 2 October 2020). Coronavirus disease 2019 is shaped by socio-economic inequalities. Transmission of SARS-CoV-2 within households is high. A large population of Manaus remains susceptible to SARS-CoV-2 after the first wave. ABSTRACT: Background: Manaus, located in the Brazilian rainforest, has experienced two health system collapses due to the coronavirus disease 2019 (COVID-19) pandemic. However, little is known about which groups among the general population have been most affected. Methods: A convenience sampling strategy via online advertising recruited 3046 adults between 19 August 2020 and 2 October 2020. Sociodemographic characteristics, COVID-19-related symptoms, COVID-19 testing, self-medication and prescribed medications were recorded. Serum anti-severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) nucleocapsid immunoglobulin G antibodies were measured with an enzyme-linked immunosorbent assay. Prevalence ratios (PR) were obtained using cluster-corrected and adjusted Poisson's regression models. Results: A crude positivity rate among asymptomatic and symptomatic individuals was estimated at 29.10%, with maximum possible seroprevalence of 44.82% corrected by test characteristics and an antibody decay rate of 32.31%. Regression models demonstrated a strong association towards marginalized low-income and vulnerable residents with limited access to health care. The presence of a COVID-19 case [PR 1.39, 95% confidence interval (CI) 1.24–1.57] or death (PR 2.14, 95% CI 1.74–2.62) in a household greatly increased the risk of other household members acquiring infection. The seroprevalence of SARS-CoV-2 was higher among those who self-medicated to prevent infection (PR 1.36, 95% CI 1.27–1.46). Conclusions: Disproportionate socio-economic disparity was observed among the study participants. The syndemic nature of COVID-19 in the Amazon region needs differential policies and urgent solutions to control the ongoing pandemic.